Developing a New Capital City (IKN) In Indonesia: A Thematic Analysis - Anirwan, Anirwan; Aljurida, A. M. Azhar; Baharuddin, Tawakkal (Policy & Governance Review, 2024)
The urgency of this research was identified from the ambitious new capital city (IKN) development project. This research aims to respond to this issue by studying the development plan. The method chosen is qualitative with a thematic analysis approach. The research data source comes from the official government website by searching official documents. The analysis tool that is maximized in data coding is Nvivo 12 Plus. This study mapped three critical themes in the IKN development plan, including the principles of development of the new capital city (IKN), the position and specificities of the new capital city (IKN), and the government's strategic efforts. In general, the IKN development theme focuses on an Indonesia-centric development orientation, development, and adaptation to the use of renewable technology and the clean technology industry for more environmentally friendly mobility and utilities, as well as accelerating the transformation of the Indonesian economy. This idea requires a government response by developing supporting infrastructure, including budget, governance, bureaucracy, and resources, and maintaining the social situation in development areas. This study is of academic interest because it provides insight into the principles and strategies underlying the development of Indonesia's new capital city (IKN), contributing to scientific discourse on sustainable development and government initiatives.